SISTEM INFORMASI DAN DIGITALISASI PENDIDIKAN : STUDI KASUS DI SEKOLAH ISLAM TERPADU INSAN MULIA BALIKPAPAN - Eriyan Ihza Nakazima, Dendi; Dayanti, Reski; Sudadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information technology has shifted educational governance from manual to digital systems. However, digitalization is often understood only as an administrative tool, not a strategic instrument for decision-making. This article aims to analyze the implementation of information systems and digitalization at the Insan Mulia Integrated Islamic School (SIT) in Balikpapan. Using a case study approach, it was found that digitalization remains partial and fragmented through the use of separate platforms such as WhatsApp, Google Classroom, and spreadsheets. This gap is caused by a lack of integrated system design, variations in the digital literacy of educators, and an immature organizational culture. Strengthening human resource capacity and developing an integrated platform aligned with Islamic values are needed to sustainably improve the quality of education.